PIMT Binding to C-Terminal Ala459 of CAIX Is Involved in Inside-Out Signaling Necessary for Its Catalytic Activity - Veronika Simko (International Journal of Molecular Sciences, 2020)
Human carbonic anhydrase IX (CAIX), a unique member of the α carbonic anhydrase family, is a transmembrane glycoprotein with high enzymatic activity by which CAIX contributes to tumorigenesis through pH regulation. Due to its aberrant expression, CAIX is considered to be a marker of tumor hypoxia and a poor prognostic factor of several human cancers. Hypoxia-activated catalytic function of CAIX is dependent on posttranslational modification of its short intracellular domain. In this work, we have identified that C-terminal Ala459 residue, which is common across CAIX of various species as well as additional transmembrane isoforms, plays an important role in CAIX activation and in pH regulation. Moreover, structure prediction I-TASSER analysis revealed involvement of Ala459 in potential ligand binding. Using tandem mass spectrometry, Protein-L-isoaspartyl methyltransferase (PIMT) was identified as a novel interacting partner, further confirmed by an in vitro pulldown assay and an in situ proximity ligation assay. Indeed, suppression of PIMT led to increased alkalinization of culture media of C33a cells constitutively expressing CAIX in hypoxia. We suggest that binding of PIMT represents a novel intracellular signal required for enzymatic activity of CAIX with a potential unidentified downstream function.